STUDI VARIASI JENIS MATERIAL TALI PADA MODIFIKASI ALAT PENGUKURAN TORSI POMPA SENTRIFUGAL - Taufik Afandi; Edi Widodo; Prantasi Harmi Tjahjanti; Iswanto Iswanto (Otopro, 2021)
The focus of this research is to analyze variations in the type of rope material and size as a link for measuring the force on a centrifugal pump, namely to find out the type of material and the size of the rope that is suitable to minimize the loss of force contained in the wire. To find out the type of calculation and comparison of the values for various types of material. From the tensile test that has been done, the highest UTS (Ultimate Tensille Stress) value was obtained in a polypropylene monofilament rope specimen with a stress value of 602.17 kgf with 382.14% elongation. The highest stress calculation value data was obtained by the Polypropylene monofilament rope specimen with a value of 738,85 at elongation to 360%. The highest modulus of elasticity obtained by Nylon rope was 4,564  . This shows that the modulus of elasticity is inversely proportional to the stress value, which was the stress value of nylon straps that was the highest compared to other specimens but had the highest elastic modulus value among other specimens.